Trapped fast MGD waves in dayside magnetosphere - Voshchepynets, A.; Agapitov, O. (Advances in Astronomy and Space Physics, 2012)
We studied the dynamics of the magnetosphere response to the solar wind parameters changes using the Alfvén velocity distribution in the Earth's magnetosphere obtained from the IGRF and T89 Earth's magnetic field models and plasma density diflusive equilibrium model. We used the solution of the eigenvalue problem for trapped waves in the dayside magnetosphere cavity as the initial condition for simulation. Numerical simulation of the fast MHD wave packet propagation in 3D magnetosphere cavity shows the occurrence of two global quasi-periodic modes of the dayside magnetosphere: cavity modes at the sub-solar region and waveguide modes at the magnetosphere flanks. The periods obtained in the numerical simulation are consistent with the theoretical predictions and the THEMIS measurements.